An axiomatic treatment of enlarged separation portfolios and treasurer's portfolios (with applications to financial synthetics) - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2009)
Expanded separation portfolios ( Se ) and Treasurer's portfolios T( Se ) are a sect of themselves. They arise out of risk-free assets and risky portfolios like other mutual funds. But their distinctive features set them apart from the common lot. This paper puts forth, firstly, a down-to-earth axiomatic that allows a complete formalization of the class of Se portfolios. Secondly, simple separation portfolios are featured and their differences with ( Se ) are highlighted. Next, the category of T( Se ) will be defined and their main properties brought to light. Last of all, there will be an expansion on the building of financial synthetics by means of enlarged separation portfolios.
Keywords: G10; G11; G24; 330; enlarged separation portfolios; mutual funds; separation portfolios; treasurer's portfolios; financial synthetics; portfolio management